Cenários climáticos futuros: diagnóstico prospectivo do desempenho termoenergético de edifícios comerciais no Brasil para o século XXI - Casagrande, Bruna Gomes (2013)
At the same time that programs were developed in Brazil with the goal of the national energy system rationalization, mainly motivated by the crisis faced by the country as in the rationing of 2001 studies of the climate s behavior on a global scale showed significant advances, facilitated by technological and computational development. One of the strategies for containment the waste energy produced is the energy consumption by buildings, since the adoption of appropriate constructive systems can reduce the final electricity consumption. This was a principle of bioclimatic architecture, which recommends an adaptation of the building to the local climate conditions, and for that, it is essential to understand the climate system. Therefore, the principle that guided the development of this research was the variable behavior of the climate, which is consensus for most climatologists, and its consequences for the future energy demands of buildings, particularly along the planned life cycle for each building. The main objective of this study was to investigate the impact of projected changes to the climate over the twenty-first century in the thermo energetic performance of commercial buildings artificially acclimatized located in different cities of Brazil. The methodological procedures were divided into four stages, initiating with an extensive literature review on the central theme climate change as well as related topics, with special emphasis on the relationship between thermal comfort and energy issue. In the second step mechanisms for preparing future climate files were established, including the selection of cities for representation of different geo-climatic conditions of the Brazilian territory. After that the definition of the object was performed, indicating the control parameters and variables in the analysis, assigning the characteristics of the building that will not be affected by future interventions window wall ratio, solar shading and orientation of the largest facades. The final step was dedicated to the simulations, performed in the program DesignBuilder from the configuration of the 192 parametric models. The results of applying the methodology, analyzed quantitatively and qualitatively, reproduced in generalized way an increase in energy consumption in buildings by 10.7% in 2020, 16.9% in 2050 and 25.6% in 2080, compared to current consumption. Although the significance of this increase, including the national energy planning, most significant increases were recorded in international studies, reinforcing the need for consideration of regional climate events in the preparation of future climate data in this type of research. In Recife, the variation of constructive parameters did not cause as significant differences in the rates of increase in consumption as the other five locations, and Brasilia had the highest rates of increase. Considering the buildings of all the cities, the presence of solar shading was the variable with the greatest impact on reducing energy consumption, and the building oriented east and west, with large unprotected openings, showed energy consumption significantly superior to other models, in all cities and periods. Finally, unlike most of monthly results observed, in Porto Alegre occurred a decrease in energy consumption in some months of 2020 and 2050, possibly caused by the reduction in time use of artificial air conditioning heating.